(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
تناول البحث في القسم الأول مآل وحدة المكان في نظرية الأدب وتطوراتها الجمالية والدلالية من التعالق الزمكاني إلى شموليتها للفضاء الأدبي، وتقصى تجليات مفهوم جماليات المكان من خلال التعريب الذي غلب على جهود التأليف في المرحلة الأولى مع بدء انتشار الحداثة في سبعينيات القرن العشرين، تعرفاً على طوابع المناهج النقدية الحديثة، ولا سيما النقد الظاهراتي نداءً لنقد الوعي مع ظواهرية الصور، وانعطافاته إلى الإدراك المعرفي للفضاء أو الحيز الزمكاني. ويمحصّ البحث في القسم الثاني المفهوم وتجلياته في الممارسة النقدية من الفلسفة إلى الأدب بعامة، ثم الأجناس الأدبية، وفي مقدمتها الرواية والقصة ثم الشعر والمسرحية ملامسة للأبعاد الفكرية والرؤيوية في تحليل النصوص وإضاءة مدلولاته من خلال الاتجاهات النقدية الحداثية كالعلامية والتفكيكية والبنيوية التكوينية والتأويلية والجمالية المعرفية. وعالج البحث في القسم الثالث تطورات النقد التطبيقي التي صارت إلى تعدد مفاهيم في الممارسة النقدية من المكان أو بناء المكان وخصوصياته إلى الزمكانية أو الفضاء (الحيز)، وقد تداخلت هذه المفاهيم في الرؤية النقدية لقضايا المكان، وحلل أعمال وخالد حسين حسين (سورية) وإبراهيم جنداري (العراق). وأوجزت الخاتمة مدى التطور النظري والتطبيقي نحو تأصيل مصطلح جماليات المكان في تقاليد النقد الأدبي العربي الحديث من خلال إيراد استخلاصات البحث. In the first part, the paper deals with the consequence of the unity of place in the theory of literature and its aesthetic and connotative development of harmony in time and place. It also examines the manifestation of the aesthetic of place through Arabization which dominated composition in the first phase of modernity in the seventies of the twentieth century. It, moreover, recognizes the features of the modern critical methodology, especially the phenomenological criticism, calling for the awareness of the picture and its swerving towards recognition of knowledge of space. In the second part, the research examines the concept and its consequences in the critical practice from philology to literature in general, including the novel, poetry, and drama. It shows the close connection of the intellectual dimensions and the vision of analyzing the text and enlightening their connotation through the modern critical tendencies like simiology, interpretation, deconstruction, structural constitution and knowledgeable aesthetics. In the third part, the research deals with the development of the practical criticism which turns into a variety of concepts in the critical practice of space and place. These concepts overlap in the critical vision of place, and the research analyses the works of Khaled Hussien Hussien (Syria), Ibrahim Gindary (Iraq). The conclusion gives the extent of the practical and theoretical development towards establishing the idiom of the place aesthetics in the traditions of the modern Arabic literary criticism through the returns of research conclusions.